Managing Online Product Reviews Effectively - Leif Brandes (Marketing Review St.Gallen, 2024)
Integrating research from various disciplines, this article presents a systematic approach to online reputation management that consists of four steps: assessing the status quo; setting goals; evaluating possible interventions; implementing and monitoring the interventions. For each step, several activities are discussed, and a distinction is made between whether the company hosts reviews on its own website or a third-party website. Two different online review contexts are used to illustrate how the presented approach can help increase the effectiveness of management efforts while avoiding unintended negative consequences.
Keywords: 650